Service Quality and Brand Equity Influence on Customer Satisfaction in Pegadaian Syariah Digital Simpang Peut - Uliyah, Putri Ridhotul; Asiah, Nur (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
This research was conducted at PT Pegadaian Syariah Digital Simpang Peut. With the aim of finding out whether service quality and brand equity have an influence on customer satisfaction. From the results of initial observations, the author suspects that there is a positive and significant influence between variable X on Variable Y as the hypothesis. Based on the results of the t test (partial test) for variable X1, the sig value is 0.005<0.05. and the t value shows a positive value, this means that variable X1 (Service Quality) has a positive and significant influence on variable Y (Customer Satisfaction). For the variable X2, the sig value is 0.000<0.05. and the t value shows a positive value, this means that variable X2 (Brand Equity) has a positive and significant influence on variable Y (Customer Satisfaction). Based on the results of the F ANOVA test (simultaneous test), variables X1 and X2 obtained a sig value of 0.000<0.05. and the F value shows a positive value, this means that the variables X1 and X2. simultaneously (together) have a positive and significant influence on variable Y. So the conclusion is that the hypothesis has been answered, namely Service Quality and Brand Equity have a positive and significant influence on Customer Satisfaction of PT Pegadaian Syariah Digital Simpang Peut.